Community Pharmacists' Motivation and Barriers to Providing and Billing Patient Care Services - Liesl D. Reyes; Jenny Hong; Christine Lin; Jeffrey Hamper; Lisa Kroon (MDPI AG, 2020)
Recently, California (CA) pharmacists' scope of practice has expanded to include independently prescribing self-administered hormonal contraceptives, nicotine replacement therapy medications, travel health medications, routine vaccinations, naloxone hydrochloride, and HIV preexposure and postexposure prophylaxis. However, previous reports indicate that practicing within this expanded scope has remained limited. Therefore, a 26-item, web-based survey was emailed to CA community pharmacists to assess pharmacists' knowledge, intent, and barriers to prescribing and billing for these patient care services. A total of 216 chain, supermarket-based, independent, mass merchant, and health-system outpatient pharmacists were included. The primary services provided and medications prescribed are for vaccinations and naloxone. Most pharmacists agree that engagement in and implementation of new strategies to enhance patients' access to care is important. Common barriers include patient unawareness of pharmacist-provided services, lack of payment for services, and difficulty incorporating services within pharmacy workflow. Pharmacists are confident in their ability to provide patient care services but are less knowledgeable and confident about billing for them. Enhancing promotion of pharmacist-provided services to patients, developing strategies to efficiently incorporate them into the workflow, and payment models can help overcome barriers to providing these services.